Pertumbuhan Dan Hasil Tanaman Jagung Manis (Zea mays L. Var. Saccharata) Dengan Pemberian Pupuk Hayati Pada Lahan Rawa Lebak - Mahdiannoor Mahdiannoor (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2014)
Corn is one of the cereals that are second staple food after rice. Sweet corn is was one of the many varieties of corn hybrids developed at this time. Corn plantation expansion not only on dry land, but also penetrated the lebak wetlands. Problems in the cultivation of lebak wetlands is water conditions are difficult to predict and low soil fertility. One of the solutions to increase growth and yield of sweet corn crop by using biological fertilizers. This study aims to (i) evaluate the response of growth and yield of sweet corn on the provision of biological fertilizer on lowland swamp land, (ii) determine the best dose of a biological fertilizer response showing the growth and yield of sweet corn on swampy wetlands. These experiments have been carried out in the Babirik Village, Babirik District, Hulu Sungai Utara Regencyat July - September 2013 using a randomized block design (RBD) a single factor. Factors studied were biological fertilizer dose (A) as much as 5 level, which consists of a0 = 0 l.ha-1, a1 = 3 l.ha-1, a2 = 6 l.ha-1, a3 = 9 l.ha -1, and a4 = 12 l.ha-1. The results showed that treatment of biofertilizers significantly affect plant height observations age 28 and 35 days after planting (DAP) , leaf number aged 35, 42, and 49 DAP; very significant effect on plant height age of 42 and 49 DAP, and heavy cob without cornhusk and ear length without cornhusk; no effect on the observed number of leaf age 28 DAP. With the best treatment is a3 (0.45 ml.plot-1).